Transformation of the Prosecutor's Office: A Normative Institutional Study Towards the Attorney General and Supreme Legal Advisor (Discourse Journal on Law and Society, 2025)
The Prosecutor's Office of the Republic of Indonesia (Kejaksaan RI) is currently undergoing a significant paradigmatic shift following the enactment of Law No. 11 of 2021. While historically viewed primarily as a prosecution agency (Dominus Litis) in criminal matters, the current legal landscape demands a stronger role in Civil and State Administrative Law (Datun). However, the institutionalization of the Attorney General as the "Supreme Legal Advisor" to the government remains suboptimal, often overshadowed by its repressive functions. This normative ambiguity hinders the state's ability to receive unified and binding legal opinions. This study aims to analyze the normative basis for this transformation and proposes an institutional framework to establish the Attorney General as the sole authority for state legal counsel. The research employs a normative juridical method with statutory and comparative approaches, analyzing the new Prosecutor's Law and comparing it with the Solliciteur-Generaal concept in other jurisdictions. The study finds that the 2021 amendment provides the necessary legal standing for this transformation, but it requires a competency upgrade for prosecutors to handle complex non-litigation issues. Strengthening the Attorney General's role as the Supreme Legal Advisor is essential to ensure legal certainty in government policies and prevent state financial losses.